2019
DOI: 10.3390/insects11010004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Thitarodes Armoricanus in Response to the Entomopathogenic Fungi Paecilomyces Hepiali and Ophiocordyceps Sinensis

Abstract: Thitarodes armoricanus is a medicinal and economically important Lepidopteran insect species. The larvae infected by Paecilomyces hepiali survive no more than four days, while those infected by Ophiocordyceps sinensis can survive for several months before mummification. This provides a valuable comparative system to study interactions between an insect host and different pathogenic fungi. By using the T. armoricanus genome, a time-course transcriptome analysis of the whole larvae without guts was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, SM producer strains that had been claimed to belong to Metarhizium anisopliae in the original chemical or biosynthetic papers referenced here may have now been separated from M. anisopliae (sensu stricto) and transferred to M. robertsii. 38 Similarly, an entomopathogenic 39 fungus isolated from an insect/Cordyceps sinensis natural complex 39 remains described as Paecilomyces hepiali even after its genome sequence has been published. 40 However, the genus name Paecilomyces is now restricted for fungi in the Eurotiales 41-43 thus P. hepiali is classified in Mycobank (www.mycobank.org) under that order.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…However, SM producer strains that had been claimed to belong to Metarhizium anisopliae in the original chemical or biosynthetic papers referenced here may have now been separated from M. anisopliae (sensu stricto) and transferred to M. robertsii. 38 Similarly, an entomopathogenic 39 fungus isolated from an insect/Cordyceps sinensis natural complex 39 remains described as Paecilomyces hepiali even after its genome sequence has been published. 40 However, the genus name Paecilomyces is now restricted for fungi in the Eurotiales 41-43 thus P. hepiali is classified in Mycobank (www.mycobank.org) under that order.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…A high diversity of fungal communities, with the dominant fungal phylum Ascomycota (such as Ophiocordyceps, Verticillium, larvae post infection is still an unresolved problem and an obstacle for commercial production of Chinese cordyceps (Li et al, 2016;Qin et al, 2018;Han et al, 2019). The living infected larvae might harbor the spindle blastospores in the hemolymph for several months, contrary to other entomopathogenic fungi such as Metarhizium anisopliae and Beauveria bassiana which cause the death of their host larvae within a few days (Meng et al, 2015;Rao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This exhibited a difference between volatile and non-volatile molecules over the development of O. sinensis products. Meanwhile, we have also found that gene expressions and microbial compositions were changed during the infection process in Thitarodes [57,58]. So far it is agreed that the parasitism process of O. sinensis fungus to its host ghost moth has involved complex chemical changes.…”
Section: Featured Metabolites and Their Potential Roles As New Quality Control Biomarkersmentioning
confidence: 89%